2019
DOI: 10.1155/2019/2039856
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Nuclear Factor Erythroid-2-Related Factor 2 against Mechanical Trauma-Induced Apoptosis in a Vaginal Distension-Induced Stress Urinary Incontinence Mouse Model

Abstract: Apoptosis and oxidative damage are involved in the pathogenesis and progression of stress urinary incontinence (SUI). Our previous results indicate that cell apoptosis and oxidative damage increase in a mouse model of mechanical injury-induced SUI and in fibroblasts treated with excessive mechanical strain. Nuclear factor erythroid-2-related factor 2 (Nrf2) is a well-characterized global antioxidant gene inducer that can reduce oxidative damage and apoptosis. Therefore, we predicted that Nrf2 may have a protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 27 publications
0
16
0
Order By: Relevance
“…The preparation of total protein lysates and western blotting were performed as described previously 35 . The primary antibody information was as follows: anti-CACNA1H (1:1000, ImmunoWay, YT4773), anti-β-actin (1:1000, Proteintech, 20536-1-AP), anti-MyHC (1:300, RND, MAB4470), anti-GRP78 (1:1000, Proteintech, 11587-1-AP), anti-DDIT3 (1:1000, CST, #5554), anti-SQSTM1 (1:1000, MBL, M162-3), anti-Beclin-1(1:1000, Proteintech, 11306-1-AP), anti-LC3 (1:1000, Proteintech, 14600-1-AP), anti-cytochrome C (1:1000, CST, #11940).…”
Section: Western Blottingmentioning
confidence: 99%
“…The preparation of total protein lysates and western blotting were performed as described previously 35 . The primary antibody information was as follows: anti-CACNA1H (1:1000, ImmunoWay, YT4773), anti-β-actin (1:1000, Proteintech, 20536-1-AP), anti-MyHC (1:300, RND, MAB4470), anti-GRP78 (1:1000, Proteintech, 11587-1-AP), anti-DDIT3 (1:1000, CST, #5554), anti-SQSTM1 (1:1000, MBL, M162-3), anti-Beclin-1(1:1000, Proteintech, 11306-1-AP), anti-LC3 (1:1000, Proteintech, 14600-1-AP), anti-cytochrome C (1:1000, CST, #11940).…”
Section: Western Blottingmentioning
confidence: 99%
“…ECM-related protein expression and serum or urinary biomarkers were examined in 51 studies [ 22 , 23 , 24 , 25 , 26 , 27 , 28 , 30 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 41 , 42 , 45 , 47 , 56 , 59 , 65 , 67 , 70 , 73 , 74 , 75 , 76 , 77 , 78 , 81 , 82 , 85 , 93 , 94 , 96 , 97 , 98 , 99 , 108 , 109 , 111 , 112 , 113 , 114 , 119 , 121 , 122 , 126 , 127 ]. Figure 4 shows an overview of human [ 23 , 24 , 25 , …”
Section: Resultsmentioning
confidence: 99%
“…Oxidative stress and apoptosis-related genes and proteins were examined in 18 studies [ 31 , 64 , 66 , 94 , 103 , 105 , 106 , 112 , 113 , 114 , 115 , 117 , 119 , 122 , 123 , 126 , 127 , 128 ]. One animal study showed that Nfe2l2 -knockout mice had lower LPPs after vaginal dilatation compared to wild-type C57BL/6J mice and this suggests that this antioxidant gene inducer is a potential protective factor in the development of SUI [ 122 ].…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that collagen I and III were reduced in fibroblasts from the SUI patients, and elevated collagen I and III in fibroblasts relieved symptoms of SUI [ 4 , 26 ]. In addition, by regulating proliferation, migration, apoptosis, differentiation and other functions, fibroblasts participated in pathogenesis of various diseases [ 27 30 ]. Recently, it was found that human circulating fibrocytes stimulated by PDGF BB (Platelet-derived growth factor-BB) and TGF - β1 (Transforming growth factor-β1) promoted proliferation and migration, and increased collagen I and III synthesis of human dermal fibroblasts [ 15 ].…”
Section: Discussionmentioning
confidence: 99%